Peningkatan Produktivitas Kerja Dengan Pendekatan KKNI Menggunakan Metode Full Time Equivalent (Studi Kasus di PT. Rosy Ceramindo) - Hartono, Hartono; Kevinda M, Bobby (Journal Industrial Manufacturing, 2021)
Human Resources (HR) has an important role in a company. PT. Rosy Ceramindo is one of the companies engaged in manufacturing tableware. So we need to optimize the number of employees in accordance with their workload through workload analysis. Mapping employee competencies is made based on the job description of each position then compared to the Indonesian National Qualification Framework (KKNI). The method used is the Full Time Equivalent method using Java. The optimal number of employees based on FTE calculations for the Production Department is 94 people. Mapping of competencies based on job description and KKNI for the position of Section Chief is at level 6 equivalent to S1 or D4. For the positions of Mold Operators, Body Raw Material Milling Operators, Glaze Raw Material Milling Operators, Painting Operators, Pressure Casting Operators, Casting Operators, Finishing Operators, Decal Operators, Glazing Operators, and Roll Kiln Operators and Packing Operators at the levels. 2 is equivalent to SMA / SMK / MA.Keywords : FTE, SDM, JAVA, KKNI, Productivity .